A educação de alunos com deficiência (ACD) numa escola pública municipal: um olhar dos segmentos escolares sobre inclusão - Lacet, Ivone Nunes de Oliveira (2012)
This study is an analyze of conditions for inclusion offered to disabilities students in a public school of Campina Grande/PB, with special attention to curricular and pedagogical practices developed by the school. Based on these considerations our research question is: What is the perception of the different characters on the conditions for inclusion offered by Municipal School Roberto Simonsen Campina Grande/PB? We used a qualitative methodology, using semi-structured interviews with the management, the multidisciplinary team, teachers, parents and students, as well as observation of the everyday practices of participants in school. Through interviews with the different segments and observations of teaching-learning situations (episodes) in the classrooms of this school we got different conceptions of inclusion, curriculum, and teacher training. The episodes and testimonials of the segments about inclusion showed that the school realizes inclusion as a practice beyond the enrollment and inclusion of disabilities students in regular schools. Before, it was understood that inclusion is realizing AcD as part of the school and should therefore actively participate in school life. About curriculum design was established that the curriculum should meet the learning needs of AcD. At nevertheless, we must emphasize that not all participants share this same vision, is among the professional group that also develop a traditional curriculum. When dealing on teacher training, the point that need to deploy it is a training focused on inclusive practices. Most teachers revealed that seek to strategies for the development of content and activities that attempt to address the limitations of AcD, we can confirm that statement in a portion of the classes that cater to these students by observing their daily practices. These data show the need for deeper reflections about the politics of educational inclusion that consider the differences.